2011
DOI: 10.1007/s10067-011-1924-x
|View full text |Cite
|
Sign up to set email alerts
|

Chilblain lupus induced by TNF-α antagonists: a case report and literature review

Abstract: We report the case of a 72-year-old man with history of ankylosing spondylitis, who, during the treatment with infliximab, developed painful, erythematous-violaceous plaques with later development of ulcers on his feet associated with cold exposure. Concomitantly with the appearance of these lesions, he presented increased antinuclear antibodies (ANA) titers, positivity for anti-DNA and IgM anticardiolipin antibodies, low complement levels, polyclonal hypergammaglobulinemia, and lymphopenia. He was diagnosed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…A high incidence of autoantibodies including ANAs, anti-dsDNA antibodies, anticardiolipin antibodies, anti-histone antibodies, anti-nucleosome antibodies and antineutrophil cytoplasmic antibodies positivity was noted in these patients (100,101). Several recent case reports describe drug-induced lupus in patients treated with anti-TNF biologicals (102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112). While manifestations were varied, a common feature was the presence of autoantibodies.…”
Section: Autoimmune Adverse Eventsmentioning
confidence: 99%
“…A high incidence of autoantibodies including ANAs, anti-dsDNA antibodies, anticardiolipin antibodies, anti-histone antibodies, anti-nucleosome antibodies and antineutrophil cytoplasmic antibodies positivity was noted in these patients (100,101). Several recent case reports describe drug-induced lupus in patients treated with anti-TNF biologicals (102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112). While manifestations were varied, a common feature was the presence of autoantibodies.…”
Section: Autoimmune Adverse Eventsmentioning
confidence: 99%
“…TNF inhibitors can induce this disease [41]. However, lupus pernio secondary to sarcoidosis responded swiftly to adalimumab in one case report [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are no pathognomonic histological findings for idiopathic chilblains, but many studies describe superficial and deep perivascular lymphocytic infiltrates, with vessel wall and papillary dermal edema [ 1 , 5 - 7 ]. It has been suggested that idiopathic chilblains may be distinguished from secondary lesions seen in lupus by the presence of spongiosis, perieccrine inflammation, and dermal edema [ 1 ] in idiopathic lesions, whereas vacuolation of basal cells is more commonly seen in lupus erythematosus lesions.…”
Section: Discussionmentioning
confidence: 99%